Improving administration - some suggestions - Saxena, N.C. (1999)
This is a concept paper for a study in the Ministry of Rural Development, Government of India. This paper describes the general malaise afflicting administration in India, specially the higher civil services and the IAS working at the state and field level. It then suggests some changes towards its improvement. - Reproduced
Keywords: Public administration